The Foundations of the Entrepreneurial Society - Audretsch, David (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2019)
Just as the entrepreneurial economy is one in which entrepreneurial activity serves as a driving force underlying economic performance, the entrepreneurial society provides the institutional, policy and cultural context conducive to entrepreneurship, which in turn, shapes economic performance. By providing the foundations of the entrepreneurial society, this addresses an inherent paradox – the impact of entrepreneurship on economic performance is embedded in a considerably broader range of influences. This suggests that a focus solely restricted to institutions, policies and culture promoting entrepreneurship is too narrow and may not necessarily generate the public policy goal of a stronger economic performance. This paper concludes that rather than a simple and singular focus on entrepreneurship, effective entrepreneurship policy needs to be compatible with the other main forces shaping and influencing spatial economic performance.